Mobile App Secure Authentication for Unified Software Architecture for Smart Computing IoT Devices - Chadha, Dr. Raman; ., Naveen; Khullar, Dr. Sunil; Kaushik, Vinita (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 10 No 1&2 (2023): Journal of Advanced Research in Instrumentation and Control Engineering, 2023)
IoT devices connect everything to the internet in this century. This allows users to remotely access and operate their equipment. Internet of Things (IoT) gadgets save time, allow remote access to resources, and connect things to the Internet. Since its inception, the Internet of Things (IoT) business has faced many difficulties, most of which involve data security. Only security authentication can establish a dependable system. Confidentiality and integrity are crucial to authentication. The Internet of Things protocols now offers varied degrees of authentication and authorization-based security. As time goes on, security against masquerade attacks, man-in-the-middle attacks, replay attacks, password-guessing Impounder assaults, DoS attacks, and others will require more protection at different stages. Because there are various sorts of system attacks. We used a DHT22 temperature sensor and a Node MCU to analyze security and find a clever solution. We received the data at Mobile via the Internet of Things protocol. We study secure data transfer from the Internet of Things devices to mobile devices. We also highlight our prototype development issues and solutions. We are also working on a prototype that reliably transmits data from Internet of Things devices to the cloud and from the cloud to mobile devices. We also focus on data transmission security from Internet of Things devices to the cloud. Keywords: IoT, Security, Authentication, Secure Sockets Layer, IoT Devices, Iot Mobile Applications